2019
DOI: 10.1371/journal.pone.0222018
|View full text |Cite|
|
Sign up to set email alerts
|

Lack of association between hypothyroxinemia of prematurity and transient thyroid abnormalities with adverse long term neurodevelopmental outcome in very low birth weight infants

Abstract: IntroductionThe association between hypothyroxinemia of prematurity with neurodevelopment was controversial.ObjectivesTo compare 5 year neurodevelopmental outcomes of very low birth weight (VLBW) infants with hypothyroxinemia of prematurity against those without.MethodsRetrospective cohort study in a single tertiary neonatal centre of VLBW infants born between the year 2008 to 2011. Comparisons were made between all abnormal and normal thyroid function controls using cord thyroid function tests, thyroid functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…In our study, TT4 concentration was not an important cause of long-term neurodevelopmental impairment. Our findings are consistent with previous research [ 28 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, TT4 concentration was not an important cause of long-term neurodevelopmental impairment. Our findings are consistent with previous research [ 28 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, owing to “confounding variables” common to preterm infants, it is difficult to establish a causal relationship with the hypothyroxinemia alone. In a study of preterm infants <1500 g, a comparison of outcome in infants with and without hypothyroxinemia did not find any significant differences in neurodevelopmental, vision or hearing impairment at 5 years of age ( 40 ).…”
Section: Unique Patterns Of Thyroid Dysfunction In Preterm/low Birth Weight Infantsmentioning
confidence: 93%
“…Many studies have found adverse effects in the later life of these newborns, such as cerebral palsy and impaired cognitive functions (3,22). On the contrary, other studies did not find any association between THOP and neurodevelopmental outcome (23,24). Scratch and cols.…”
Section: Discussionmentioning
confidence: 99%